Makna Mabuk Agama pada Tayangan Channel Youtube 2045 TV - Ikhsan Khavidz; Aini Noviar, Tri Nur (Bandung Conference Series: Journalism, 2025)
Abstract. Religious drunkenness refers to the behavior of someone who practices religious teachings excessively, to the point of ignoring knowledge and healthy thinking. Individuals who experience religious drunkenness tend to ignore logic, common sense, instincts of wisdom, and human empathy in order to obey religious teachings without considering moral aspects, truth, and its impact on the surrounding environment. The purpose of this study was to determine the meaning of religious drunkenness by Denny Siregar in the 2045 Tv YouTube channel. This study adopts a constructivist paradigm, using qualitative methods and Roland Barthes' semiotic approach. The data collection techniques used were observation, interviews, and documentation. The results of the study explain that the meaning of denotation, connotation, and myth of religious drunkenness is a form of anxiety about broader social and cultural conditions. Religion is often used for certain interests or becomes an obstacle to progress. Drunkenness and religion are two different things and cannot be combined. Drunkenness is something negative while religion is a guideline in life to be better or positive. The use of the term religious drunkenness by Denny Siregar is considered inappropriate, because it only describes the form of his anxiety towards people who use religion not according to its intended use. Abstrak. Mabuk agama merujuk pada perilaku seseorang yang mengamalkan ajaran agama secara berlebihan, hingga mengabaikan pengetahuan dan pemikiran yang sehat. Individu yang mengalami mabuk agama cenderung mengesampingkan logika, akal sehat, naluri kebijaksanaan, dan empati kemanusiaan demi mentaati ajaran agama tanpa mempertimbangkan aspek moral, kebenaran, serta dampaknya terhadap lingkungan sekitar. Tujuan dari penelitian ini adalah untuk mengetahui makna mabuk agama Dennny Siregar dalam channel youtube 2045 Tv Penelitian ini mengadopsi paradigma konstruktivisme, menggunakan metode kualitatif dan pendekatan semiotika Roland Barthes. Teknik pengumpulan data yang digunakan adalah observasi, wawancara, serta dokumentasi. Hasil penelitian menjelaskan bahwa makna denotasi, konotasi, dan mitos mabuk agama merupakan bentuk keresahan terhadap kondisi sosial dan budaya yang lebih luas. Agama seringkali dimanfaatkan untuk kepentingan tertentu atau justru menjadi penghalang bagi kemajuan. Mabuk dan agama merupakan dua hal berbeda dan tidak bisa dijadikan satu. Mabuk suatu hal yang negatif sedangkan agama merupakan pedoman dalam berkehidupan agar menjadi lebih baik atau positif. Penggunaan istilah mabuk agama oleh Denny Siregar dirasa kurang tepat, karena hanya sekedar menggambarkan bentuk keresahannya kepada orang yang menggunakan agama tidak sesuai dengan peruntukannya.